Study on the Stage Method of the Water Environmental Capacity Flood Season in the Ningxia Section of the Yellow River - Yu Song; Hongrui Wang (Hydrology)
The rational use of the water environmental resources of the main stream of the Yellow River, which is the mother river of the Chinese nation, and the control of and reduction in water environmental pollution, especially in relation to water quality safety, have become important issues that must be considered in Ningxia’s economic and social development. Due to the influence of monsoons, river runoff in most of the river basins in China is mainly concentrated in the flood season, and its distribution is extremely uneven within and among years. Therefore, an analysis of the seasonal change law of heavy rainfall and flooding and a scientific and rational staging of the flood season can fully demonstrate the comprehensive benefits of the river and also address the inevitable need to master and utilize the capacity of the water environment. In this study, the abundant, level, and absent year division of the Ningxia section of the main stream of the Yellow River was carried out using the percentage of parity and the guarantee rate methods. Several commonly used flood periods staging methods were studied, and their applicable conditions were preliminarily analyzed. The research results not only provide a reference for the relevant management departments, a decision-making basis for rational planning, and the scientific and appropriate development of river basins but they also have scientific research significance.